Odpowiedź :
Liczę na naj.
x = 2, y = -3
a) (x + y) + (x - 4) - (5 - y) = x + y + x - 4 - 5 + y = 2x + 2y - 9
2 * 2 + 2 * (-3) - 9 = 4 - 6 - 9 = -11
b) -(2x + y) - (3 - x) + (2y - 5) = -2x - y - 3 + y + 2y - 5 = -2x + 2y - 3
-2 * 2 + 2 * (-3) - 3 = -4 - 6 - 3 = -13
c) (3x - y + 1) - (x + y) + (y - x) = 3x - y + 1 - x - y + y - x = x - y + 1
2 + 3 + 1 = 6
d) -(2[tex]x^{2}[/tex] - 3xy) - (2y - 3[tex]x^{2}[/tex]) + (-xy - y) = -2[tex]x^{2}[/tex] + 3xy - 2y + 3[tex]x^{2}[/tex] - xy - y = [tex]x^{2}[/tex] + 2xy - 3y
[tex]2^{2}[/tex] + 2*2*(-3) - 3*(-3) = 4 - 12 + 9 = 1